High flow oxygen and risk of mortality in patients with a suspected acute coronary syndrome: pragmatic, cluster randomised, crossover trial. (2nd March 2021) - Stewart, Ralph A H; Jones, Peter; Dicker, Bridget; Jiang, Yannan; Smith, Tony; Swain, Andrew; Kerr, Andrew; Scott, Tony; Smyth, David; Ranchord, Anil; Edmond, John; Than, Martin; et al.
Abstract: Objective: To determine the association between high flow supplementary oxygen and 30 day mortality in patients presenting with a suspected acute coronary syndrome (ACS). Design: Pragmatic, cluster randomised, crossover trial. Setting: Four geographical regions in New Zealand. Participants: 40 872 patients with suspected or confirmed ACS included in the All New Zealand Acute Coronary Syndrome Quality Improvement registry or ambulance ACS pathway during the study periods. 20 304 patients were managed using the high oxygen protocol and 20 568 were managed using the low oxygen protocol. Final diagnosis of ST elevation myocardial infarction (STEMI) and non-STEMI were determined from the registry and ICD-10 discharge codes. Interventions: The four geographical regions were randomly allocated to each of two oxygen protocols in six month blocks over two years. The high oxygen protocol recommended oxygen at 6-8 L/min by face mask for ischaemic symptoms or electrocardiographic changes, irrespective of the transcapillary oxygen saturation (SpO2 ). The low oxygen protocol recommended oxygen only if SpO2 was less than 90%, with a target SpO2 of less than 95%. Main outcome measure: 30 day all cause mortality determined from linkage to administrative data. Results: Personal and clinical characteristics of patients managed under both oxygen protocols were well matched. For patients with suspected ACS, 30 day mortality for the high and low oxygen groups was 613 (3.0%) and 642 (3.1%), respectively (odds ratio 0.97, 95% confidence interval 0.86 to 1.08). For 4159 (10%) patients with STEMI, 30 day mortality for the high and low oxygen groups was 8.8% (n=178) and 10.6% (n=225), respectively (0.81, 0.66 to 1.00) and for 10 218 (25%) patients with non-STEMI was 3.6% (n=187) and 3.5% (n=176), respectively (1.05, 0.85 to 1.29). Conclusion: In a large patient cohort presenting with suspected ACS, high flow oxygen was not associated with an increase or decrease in 30 day mortality. Trial registration: ANZ Clinical Trials ACTRN12616000461493.